HUBUNGAN ANTARA FAKTOR FAKTOR YANG BERPENGARUH TERHADAP KUALITAS HIDUP PENDERITA MYASTHENIA GRAVIS DI RSUP DR HASAN SADIKIN BANDUNG - Swastika*, Nani Kurniani**, Thamrin Syamsudin** (NEURONA, 2011)
INTRODUCTION MYASTHENIA GRAVIS MG IS A RARE AUTOIMMUNE DISEASE PATIENTS WITH MG CAN LIVE LONGER WITH TREATMENT AND EFFECTIVE THERAPY THAN IT WAS 30 YEARS AGO THE AIM OF THIS STUDY IS TO DESCRIBE CORRELATION FACTORS THAT AFFECT QUALITY OF LIFE IN PATIENTS WITH VARIOUS TYPES OF MYASTHENIA GRAVIS